Acute kidney injury is under‐recognised and under‐reported in hospitalised patients in Australia. Issue 12 (10th December 2017) - Mitchell, Tim; Feher, Elisabeth; Mitchell, Gillian; Chakera, Aron
Abstract: Acute kidney injury (AKI) in hospitalised patients is associated with adverse outcomes; however, it remains unrecognised and under‐reported. A total of 48 045 serum creatinine results from 8129 tertiary hospital inpatients were reviewed. The prevalence of AKI was 4.33%. Mortality was significantly higher in patients with AKI (16.76%) compared to those without AKI (1.88%, P < 0.001). Documentation of AKI in discharge summaries was poor.